2015
DOI: 10.1016/j.patcog.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Principles of time–frequency feature extraction for change detection in non-stationary signals: Applications to newborn EEG abnormality detection

Abstract: This paper considers the general problem of detecting change in non-stationary signals using features observed in the time-frequency (t, f) domain, obtained using a class of quadratic timefrequency distributions (QTFDs). The focus of this study is to propose a methodology to define new (t, f) features by extending time-only and frequency-only features to the joint (t, f) domain for detecting changes in non-stationary signals. The (t, f) features are used as a representative subset characterizing the status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 37 publications
0
60
0
Order By: Relevance
“…If the entropy of a TFD is to be calculated without using its singular values, the Time-Frequency Rényi entropy (TFRE) in been replaced with the corresponding twodimensional TF characteristics according to [30]. ▶ Table 3 includes all extended time-domain features.…”
Section: Entropy-based Tfd-derived Featuresmentioning
confidence: 99%
“…If the entropy of a TFD is to be calculated without using its singular values, the Time-Frequency Rényi entropy (TFRE) in been replaced with the corresponding twodimensional TF characteristics according to [30]. ▶ Table 3 includes all extended time-domain features.…”
Section: Entropy-based Tfd-derived Featuresmentioning
confidence: 99%
“…Most of the existing abnormality detection methodologies require visual analysis by a neurophysiologist. Detection of abnormality in EEG signal is a non-stationary signal classification problem that involves extraction of features from time-domain, frequency domain or joint t-f domain representations of signal [1][2][3][4][5][6]. Recent studies have indicated that EEG signals have non-stationary characteristics, so time-frequency methods are preferred tools for their analysis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Quadratic Time-Frequency Distributions (TFD) are frequently employed for analysis and extraction of features from EEG signals because of their high resolution [4]. The Wigner-Ville Distribution (WVD) is a core distribution of this class.…”
Section: Introductionmentioning
confidence: 99%
“…Much research focuses on specific patterns: for example, neonatal seizure detection and localisation [29,[35][36][37], and detection of the sleep-wake cycle [38]. Classification of a broader variety of EEG background patterns will increase the system complexity and the need for specific EEG data, especially in long-term multichannel EEG recordings.…”
Section: Significance and Motivationmentioning
confidence: 99%
“…Most research has focused on specific patterns: for example, seizure detection and localisation [29,[35][36][37], burst-suppression classification [24,[152][153][154] and detection of the sleep-wake cycle [38]. Classification of a broader variety of EEG background patterns will increase the system complexity.…”
Section: Visual Inspection Of the Eeg Signal Is Routine But Visual Inmentioning
confidence: 99%